The Effects of Personality, Family Functioning and Perceived Social Support on Suicide: Suicide Risk Among Individuals in Turkish Probation System - Görgülü, Tuğba; Işıkhan, Vedat (The Bulletin of Legal Medicine, 2019)
Each year, an average of one million people end their lives by suicide. This rate is higher for disadvantaged groups such as the criminal population and substance users.  Psychiatric problems and certain social factors increase suicide risk. Although the criminal involved and substance users have been studied in Turkey, research on suicide risk factors are limited. Therefore, the aim of this study is to examine the effects of personality traits, and psychosocial variables such as family functioning, and perceived social support on suicide risk in individuals directed to Turkish probation services. Participants were 403 males, of which 183 were substance users and 220 were criminals. Results, revealed a significant relationship between being single, low income, criminal behavior at an early age, substance use behavior, multiple drug use, and suicide risk. Additionally, personality traits of neuroticism and psychoticism, as well as family members’ interest in each other were found to be best predictive variables of suicide risk R2= 0.551, F (12, 389) = 39.79, p
Keywords: substance use; criminality; personality; family functioning; perceived social support; suicide risk